The cryoconite of the Thule area - Gerdel, Robert W.; Drouet, Francis, 1907-1982 joint author. (Wilmette, Ill. : U.S. Army Snow Ice and Permafrost Research Establishment, Corps of Engineers, 1958)
Mode of access: Internet.